H2S Mediated One-Pot Synthesis of Single Phase Hexagonal CoS Nano-Spheres: A Pseudocapacitive Electrode for Hybrid Supercapacitors - Kushwaha V.; Mondal R.; Mandal K.D.; Singh P.; Gupta A. (My University, 2025)
Due to their exceptional qualities like high power density, extended cycle life, quick response, rapid charging periods, higher capacitance, and moderate energy density, hybrid (Asymmetric) supercapacitors (HSCs) have become a potential energy storage option as bulk energy storage devices to harness the renewable energy generated through sources such as solar, wind and tidal as an alternative to fossil fuels. Single-phase hexagonal CoS nano-sphere was successfully synthesized via the H2S-mediated one-pot synthesis route, characterized by crystallographic and microscopic techniques, and further investigated as a potential pseudocapacitive electrode material for use in large-scale energy storage systems. The CoS electrode showed a superior specific capacitance of 761 F/g at 1 A/g current density from the galvanostatic discharge profile, and a capacitance of 776 F/g at 1 mV/s from the CV curve in 2 M KOH aqueous electrolyte. An aqueous asymmetric hybrid supercapacitor (HSC) device was assembled with activated carbon (AC) as the negative electrode and the CoS as the positive electrode. The device (full cell in HSC mode) results in high energy and power densities of 139.7 Wh/kg and 7.51 kW/kg, respectively, with excellent cyclic stability of up to 87 % after 10000 continuous charge-discharge cycles. The electrochemical measurements demonstrate high-rate capacity and good cyclic stability of the CoS nano-sphere, suggesting a great potential to be used as a supercapacitor electrode. © 2023 Wiley-VCH GmbH.